The Use of Qualitative Business Tendency: Surveys for Forecasting Business Investmentin Germany - Klaus Abberger (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2005)
Investment in equipment and machinery is a very important component of GDP. In this paper we examine whether data from business tendency surveys are useful for a timely assessment of current investment behavior. In addition we investigate whether the survey results are helpful for forecastinginvestment growth in the short run. The first question is addressed with thehelp of spectral analysis. To study the forecast ability we estimate linearautoregressive and additive autoregressive models. The forecasting performance is assessed through filtered residuals. The analyses show that the business survey is indeed a useful tool for assessing investment in equipment and machinery.
Keywords: C20; C40; 330; Business tendency surveys; forecasting; investment; linear autoregression; additive autoregression